Analytical spontaneous imbibition model for confined nanofractures. (18th May 2020) - Zeng, Fanhui; Zhang, Qiang; Guo, Jianchun; Zhang, Yu; Ren, Wenxi; Jiang, Qifeng; Xiang, Jianhua
Abstract: The capillary spontaneous imbibition length of slick water in confined rectangular cross-sectional nanofractures is investigated in this paper. In the established model, the effective slip length, effective viscosity, wettability and nanofracture size are incorporated into the modified Hagen– Poiseuille equation. The calculated spontaneous imbibition length as a function of time, viscosity, wettability and pore size is qualitatively validated by experimental and previous theoretical Hagen– Poiseuille flow results. Our model calculation results agree well with the published experimental data. The ratio of the effective and bulk water viscosities is higher than one, and increases with an increase in the ratio of the nanofracture width to height and decreasing contact angle. The spontaneous imbibition capacity of confined water is enhanced ∼0.67– 1.28 times, as determined by the Hagen–Poiseuille equation without the slip effect for various contact angles and nanofracture dimensions.